A Systematic, Intensive Statistical Investigation of Data from the Comprehensive Analysis of Reported Drugs (CARD) for Compliance and Illicit Opioid Abstinence in Substance Addiction Treatment with Buprenorphine/naloxone. (28th January 2018) - Blum, Kenneth; Han, David; Modestino, Edward J.; Saunders, Scott; Roy, A. Kennison; Jacobs, W.; Inaba, Darryl S.; Baron, David; Oscar-Berman, Marlene; Hauser, Mary; Badgaiyan, Rajendra D.; Smith, David E.; et al.
ABSTRACT: Background : Buprenorphine and naloxone (bup/nal), a combination partial mu receptor agonist and low-dose delta mu antagonist, is presently recommended and used to treat opioid-use disorder. However, a literature review revealed a paucity of research involving data from urine drug tests that looked at compliance and abstinence in one sample. Method : Statistical analysis of data from the Comprehensive Analysis of Reported Drugs (CARD) was used to assess compliance and abstinence during treatment in a large cohort of bup/nal patients attending chemical-dependency programs from eastern USA in 2010 and 2011. Results : Part 1: Bup/nal was present in 93.4% of first ( n = 1, 282; p <.0001) and 92.4% of last ( n = 1, 268; p <.0001) urine samples. Concomitantly, unreported illicit drugs were present in 47.7% ( n = 655, p =.0261) of samples. Patients who were compliant to the bup/nal prescription were more likely than noncompliant patients to be abstinent during treatment ( p =.0012; odds ratio = 1.69 with 95% confidence interval (1.210, 2.354). Part 2: An analysis of all samples collected in 2011 revealed a significant improvement in both compliance ( p < 2.2 × 10 −16 ) and abstinence ( p < 2.2 × 10 −16 ) during treatment. Conclusion/Importance : While significant use of illicit opioids during treatment with bup/nal is present, improvements in abstinence and high compliance during maintenance-assisted therapy programs may ameliorate fears of diversion in comprehensive programs. Expanded clinical datasets, the treatment modality, location, and year of sampling are important covariates, for further studies. The potential for long-term antireward effects from bup/nal use requires consideration in future investigations.